Association of non-optimum temperature, heatwaves and cold spells with chronic obstructive pulmonary disease mortality: A nationwide time-stratified case-crossover study - Kexin Yu; Shuo Jiang; Su Shi; Xia Meng; Renjie Chen; Haidong Kan; Peng Yin; Maigeng Zhou; Feng Tan; Cong Liu; Xunliang Tong (Ecotoxicology and Environmental Safety, 2025)
Background: Climate change intensifies temperature instability and leads to an increase in extreme weather events. This study aimed to examine the effect of non-optimum temperatures, heatwaves, and cold spells on mortality risk of chronic obstructive pulmonary disease (COPD). Methods: This study employed a time-stratified case-crossover design among 2260,692 COPD decedents from a national death registration repository in China. Daily mean temperature was derived from ERA5 dataset. Heatwaves and cold spells were defined by incorporating relative high/low temperature thresholds and duration days. To evaluate the cumulative exposure-response relationships with COPD mortality, we employed conditional logistic regressions integrated with distributed lag nonlinear models. Results: The association of daily mean temperature and COPD mortality presented an inverse J shape. Exposure to extreme cold (-5°C, 2.5th percentile) and hot (29°C, 97.5th percentile) temperatures resulted in 73.3 % and 16.4 % increases in COPD mortality risk, respectively. For cold spell days (daily mean temperature ≤10th percentile and durations ≥2d), the risk of COPD mortality increased by 10.09 % (95 % CI: 8.66 %, 11.55 %). We also observed higher COPD mortality risk associated with heatwave, defined as days with mean temperatures exceeding the 92.5th percentile for at least two consecutive days [21.28 % (95 % CI: 18.73 %, 23.89 %)]. Conclusions: This nationwide study presents evidence that non-optimum temperatures, heatwaves and cold spells could significantly increase COPD mortality risk. The findings on vulnerable populations and differential risks in different regions may contribute to the targeted prevention and alarming system.